2017
DOI: 10.1057/s41286-017-0032-z
|View full text |Cite
|
Sign up to set email alerts
|

Subjectivity in a context of environmental change: opening new dialogues in mental health research

Abstract: In a period of unstable experimentation with challenges of globalisation of associated risks, and disenchantment with 'enduring injustice', we bring forward a consideration of subjectivity to the study of environmental change and mental health. We begin by identifying how mainstream climate change and mental health studies are unable to explain the emergent and co-evolutionary pathways of agency. As a means of freeing these studies of their objective dimensions of linear-causation, we argue in favour of a repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…One gap we identified is the relationship between environmental questions, environmental impacts, and environmental approaches to subjectivity and the human psyche. Although there have been important contributions from a number of places, after 2 years of research (Barbosa, 1996;Seixas et al, 2010;Seixas & Nunes, 2017), we have discovered several missing points necessary to establishing this important relationship. We also discovered that much still needs to be identified and clarified in order to establish the support needed for dealing with the great challenges which environmental changes impose on the planet and, in turn, the quality of human life.…”
Section: Approachesmentioning
confidence: 90%
See 3 more Smart Citations
“…One gap we identified is the relationship between environmental questions, environmental impacts, and environmental approaches to subjectivity and the human psyche. Although there have been important contributions from a number of places, after 2 years of research (Barbosa, 1996;Seixas et al, 2010;Seixas & Nunes, 2017), we have discovered several missing points necessary to establishing this important relationship. We also discovered that much still needs to be identified and clarified in order to establish the support needed for dealing with the great challenges which environmental changes impose on the planet and, in turn, the quality of human life.…”
Section: Approachesmentioning
confidence: 90%
“…Some have alerted about the impacts on mental health as well, (Van Susteren, 2018, Clayton et al, 2015, Coverdale et al, 2018, Wei-Lun et al, 2018. We had the opportunity to draw attention to this in Seixas and Nunes (2017) but the identification and unfolding of these impacts on subjectivity or psyche is something we have only been able to identify recently. Now we have the opportunity to delve into these concepts here in this book.…”
Section: Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies (Obradovich et al, 2018;Seixas & Nunes, 2017) have recently indicated that the impacts of climate change are likely to effect and undermine mental health through a variety of direct and indirect mechanisms. Studies show that hotter temperatures and added precipitation both worsen mental health, and that multiyear warming is connected to an increased prevalence of mental health issues.…”
Section: Quality Of Life In a Climate Change Contextmentioning
confidence: 99%